THE IMPORTANCE OF PRESENTING COOPERATIVE FINANCIAL REPORTS TO CREATE GOOD COOPERATIVE GOVERNANCE: INDONESIA CASE - Arda, Devid Putra (Program Studi Akuntansi Institut Bisnis dan Informatika (IBI) Kosgoro 1957, 2024)
The presence of cooperatives in the Indonesian economic system is a valuable place. Article 33 of the Constitution of the Republic of Indonesia states that cooperatives are used as a foundation to support the country's economy. This is reinforced by Law Number 25 of 1992 concerning Cooperatives of the Republic of Indonesia which states that cooperatives are national economic business entities based on the principle of kinship. Indonesian cooperatives are built based on basic principles: membership is voluntary, democratically managed, independent, and services are provided in accordance with the capital contribution paid by members. The effectiveness of cooperatives is measured by the ability to carry out good cooperative management. One dimension of good cooperative governance is transparency, which is characterized by the cooperative's ability to present its financial reports fairly. The purpose of this research is to assess the ability of cooperatives to present financial reports fairly in accordance with the Indonesian Public Entity Accounting Standards (SAK ETAP). The research method used in this research is qualitative research. The number of cooperatives used as the unit of analysis in this research consists of two multi-purpose cooperatives, two savings and loan cooperatives (credit cooperatives) and one service cooperative. A total of five cooperatives are used as units of analysis. Location of all cooperatives in the DKI Jakarta area. The data collection technique used by researchers is in-depth interviews. The data analysis model used by the author is Miles and Huberman's interactive analysis. Based on the results of this research, most cooperatives prepare year-end annual reports. Only two cooperatives provide complete financial reports. Of the five cooperatives, only two cooperatives are fully implemented by SAK ETAP. The reason cooperatives are not guided by SAK ETAP is because of the limited scientific abilities of employees and carelessness of management in preparing financial reports based on SAK ETAP. The government is expected to be more active in training and developing cooperatives so that they are able to prepare economic reports fairly and completely based on SAK ETAP.